THE INFLUENCE OF SELF CONTROL, PRICES, MARKETPLACE PROMOTIONS ON IMPULSIVE BUYING IN ACCOUNTING STUDENTS - Jennifer Nydia (Income, 2024)
Globalization has transformed the business landscape, particularly in the information technology sector. Online marketplaces have become platforms facilitating the exchange of information and business transactions, speeding up access, and altering consumer purchasing patterns. The increasing ease of access to online shopping and aggressive marketplace strategies, including affordable pricing and promotions, trigger impulse buying behavior. Despite providing convenience, consumer self-control may be influenced by discount time limits and promotional situations. The research methodology employs a quantitative approach through online surveys with respondents from an accounting student background. The study aims to comprehend the impact of self-control, pricing, and promotions on impulse buying. The implications of these findings can assist businesses in designing more effective marketing strategies and enhancing accounting students' understanding of impulsive purchasing decisions.